2020
DOI: 10.3390/antiox9121299
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Reduces NLRP3 Inflammasome Activation by Increasing α7 nAChR-Mediated Autophagic Flux

Abstract: Microglia controls the immune system response in the brain. Specifically, the activation and dysregulation of the NLRP3 inflammasome is responsible for the initiation of the inflammatory process through IL-1β and IL-18 release. In this work, we have focused on studying the effect of melatonin on the regulation of the NLRP3 inflammasome through α7 nicotinic receptor (nAChR) and its relationship with autophagy. For this purpose, we have used pharmacological and genetic approaches in lipopolysaccharide (LPS)-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Suppression of the formation and activity of the NLRP3 inflammasome caused by melatonin was observed after LPS treatment in natural microglia in vivo [ 32 ] and in BV2 cells [ 33 ] as well as in an inflammation model of intracerebral hemorrhage in which BV2 cells were treated with thrombin [ 34 ]. In the latter study, conditioned medium from thrombin-treated BV2 cells was also shown to induce apoptosis in HT22 cells, an effect suppressed by the addition of melatonin.…”
Section: Melatonin Suppresses Proinflammatory and Favors Anti-inflammatory Signalingmentioning
confidence: 99%
“…Suppression of the formation and activity of the NLRP3 inflammasome caused by melatonin was observed after LPS treatment in natural microglia in vivo [ 32 ] and in BV2 cells [ 33 ] as well as in an inflammation model of intracerebral hemorrhage in which BV2 cells were treated with thrombin [ 34 ]. In the latter study, conditioned medium from thrombin-treated BV2 cells was also shown to induce apoptosis in HT22 cells, an effect suppressed by the addition of melatonin.…”
Section: Melatonin Suppresses Proinflammatory and Favors Anti-inflammatory Signalingmentioning
confidence: 99%
“…Remarkably, H 2 O 2 -treatment at a dose of 100 µM causes a robust increase in NLRP3 activation along with cleavage of caspase-1 and release of mature IL-1β level and IL-18 level in LPS primed microglia which remains as potent pro-in ammatory cytokines for further exacerbating neuroin ammatory cascade following neurodegeneration. Similar studies in microglia and macrophages have shown the NLRP3 in ammasome activation with LPS priming following extracellular ATP treatment but not with LPS or ATP alone [55,56]. Contrary to this a few studies states the in ammasome activation occurs only by LPS priming but not its downstream cascade proteins (IL-1β, IL-18) [57,58].…”
Section: Discussionmentioning
confidence: 86%
“…However, the initiation of melatonin supplementation must be carefully addressed to ensure its antiinflammatory potential [31]. However it is hypothesized that the anti-inflammatory activity of melatonin is mainly achieved by orchestrating the suppression of toll-like receptor (TLR) signaling [175], the inhibition of the multiprotein platform inflammasome promoter NLRP3 (Nucleotide-binding Oligomerization Domain (NOD)-Like Receptor Pyrin domain containing 3) [176], and the blockage of the nuclear translocation of the NF-κB [76]. The result of binding viral proteins and/or genomic ssRNA by TLR/PAMPs would be the recruitment of the receptor-ligand complexes and the activation of apoptosis, lysosomal autophagy, and inflammasome-induced pyroptosis for the clearance of the virus [166].…”
Section: Melatonin and Inflammaging In The Context Of Covid-19mentioning
confidence: 99%